Herbert Smith (1862-1938)
"Herbert Smith (1862-1938)" [T0611.jpg] Herbert Smith (1862-1938) was born near Kippax in Yorkshire and was orphaned shortly after his birth. He spent his early years in the workhouse, but was later adopted. He started working in the mines at the age of 10 and from 1879 held various union branch positions. He became president of the Yorkshire Miners' Association in 1906 and president of the Miners' Federation of Great Britain 1922-1929. During the 1926 General Strike, Smith led the miners' delegation in talks with Government and mine owners. He had a strong physical presence and was seen as the most obdurate of the miners' leaders.